Effects of ethanol, acetaldehyde and cholesteryl esters on pancreatic lysosomes. Issue 8 (August 1992) - Wilson, J S; Apte, M V; Thomas, M C; Haber, P S; Pirola, R C
Abstract : Recent studies indicate that altered lysosomal function may be involved in the early stages of pancreatic injury. Chronic consumption of ethanol increases rat pancreatic lysosomal fragility. The aim of this study is to determine whether the lysosomal fragility observed after chronic ethanol consumption is mediated by ethanol per se, its oxidative metabolite acetaldehyde or cholesteryl esters (substances which accumulate in the pancreas after ethanol consumption). Pancreatic lysosomes from chow fed rats were incubated for 30 minutes at 37 degrees C with ethanol, acetaldehyde or phosphatidylcholine vesicles containing cholesteryl oleate. Lysosomal stability was then assessed by determination of: (a) Latency–that is, the per cent increase in lysosomal enzyme activity after addition of Triton X-100 and (b) Supernatant activity–that is, the proportion of lysosomal enzyme remaining in the supernatant after resedimentation of lysosomes. Acid phosphatase, N-acetyl glucosaminidase, beta-glucuronidase and cathepsin B were assayed as lysosomal marker enzymes. Lysosomes incubated with homogenising medium alone or equivalent volumes of phosphatidylcholine vesicles without cholesteryl oleate were used as controls. Cholesteryl oleate at concentrations of 15 and 20 mM increased pancreatic lysosomal fragility as shown by decreased latency and increased supernatant enzyme. In contrast, ethanol (150 mM) and acetaldehyde (5 mM) had no effect on lysosomal stability in vitro. These results suggest that increased pancreatic lysosomal fragility observed with ethanol may be mediated by cholesteryl ester accumulation rather than by ethanol or acetaldehyde.